2018
DOI: 10.1097/scs.0000000000004859
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 Deletion: Surgical and Speech Outcomes of Patients With Velopharyngeal Insufficiency Treated With a Superiorly Based Pharyngeal Flap as the Primary Surgery

Abstract: The most frequent palate diagnoses in patients with chromosome 22q11.2 deletion syndrome are a classic submucous cleft, occult, and velopharyngeal insufficiency without cleft, which generates alterations in speech that require surgery. Surgical protocols are controversial owing to syndrome characteristics that make their handling more complex. Pharyngeal flap pharyngoplasty is effective for this type of patient. The objective of this study is to examine the surgical management of velopharyngeal insufficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…49 Carvajal et al also demonstrated satisfactory postoperative outcomes in patients with 22q11.2 deletion syndrome treated by pharyngeal flap repair. 50 Like Bezuhly et al, the authors concluded that patients with 22q11.2 deletion syndrome can be safely treated with surgical repair, but pre-operative planning must be performed so that individualised treatment can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…49 Carvajal et al also demonstrated satisfactory postoperative outcomes in patients with 22q11.2 deletion syndrome treated by pharyngeal flap repair. 50 Like Bezuhly et al, the authors concluded that patients with 22q11.2 deletion syndrome can be safely treated with surgical repair, but pre-operative planning must be performed so that individualised treatment can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…It is important, after this analysis, to follow clear diagnostic study guidelines, as suggested in other studies. A different scheme is applied in those with SMCP, chromosome 22 microdeletion, and severe VPI, where the indication for a custom flap has been protocolized after performing nasopharyngoscopy 40 …”
Section: Discussionmentioning
confidence: 99%